Technology-Enhanced Integration of Medical Entomology into General Medical Education: Innovations in Science and Technological Pedagogy - Abbasi, Ebrahim (META: Journal of Science and Technological Education, 2025)
Medical entomology plays a critical role in understanding vector-borne diseases, yet its integration into general medical education remains limited, leading to gaps in physician preparedness. Advancements in science and technological education offer opportunities to strengthen curricular inclusion through innovative pedagogical approaches. This study employed a mixed-methods design combining curriculum analysis, expert interviews, and technological assessments across multiple medical schools in Iran. Data were systematically analyzed to evaluate the extent, methods, and effectiveness of medical entomology instruction, including the role of technology-enhanced tools. The findings indicate that medical entomology is frequently marginalized in curricula, with minimal practical exposure. Institutions that implemented digital tools such as simulations, geographic information systems, and interactive learning modules demonstrated improved student engagement and perceived relevance. Expert interviews emphasized that technology-mediated approaches facilitated applied understanding, competency development, and alignment with real-world clinical and public health challenges. Structural limitations, including faculty expertise and institutional constraints, were identified as barriers, while technology-enhanced strategies were found to help mitigate these challenges. Integrating medical entomology through technological innovations enhances student engagement, practical competencies, and interdisciplinary understanding, addressing both educational and public health needs. This study highlights the potential of technology to bridge curricular gaps, promote learning equity, and better prepare future physicians for emerging vector-borne disease challenges.